The Effect of Using Prodigy Math Game on Elementary School Students’ Literacy, Numeracy, and Critical Thinking Skills - Taufik Taufik; Muhajir Muhajir; Ahmad Hatip (Journal of Social Work and Science Education, 2026)
The purpose of this study is to assess how the Prodigy Math Game improves elementary school kids’ reading, numeracy, and critical thinking skills. The study employed a quasi-experimental approach with a pretest-posttest control group. The research sample consisted of Class 6A, comprising 24 students, who served as the experimental group and used the Prodigy Math Game in the learning process. Class 6B, also consisting of 24 students, functioned as the control group and received instruction through conventional teaching methods. The research tools included literacy, numeracy, and critical thinking assessments, as well as observation sheets and interviews to assess student participation. The study found that pupils in the experimental group improved significantly in literacy, numeracy, and critical thinking compared to the control group. The experimental group’s average posttest score was considerably higher, according to a t-test. Students’ ability to grasp text-based questions in the game indicated better reading, and their ability to answer math problems of various difficulty exhibited improved numeracy. Critical thinking skills are developed by using proper problem-solving tactics in games. These findings lend credence to a constructivist approach to learning, which stresses hands-on experience and personalized challenges. This study found that the Prodigy Math Game is an excellent, innovative way to improve primary school children’ literacy, numeracy, and critical thinking skills.